Extrusion of power-law shear-thinning fluids with small exponent - Chapman, S; Fitt, A; Please, C (1997)
The slow flow of power-law shear-thinning fluids during extrusion is considered for materials where the exponent is asymptotically close to zero. Such flows arise in a number of practical industrial problems and give rise to some unexpected effects. Three different regions of extrusion flow are examined. First, some simple results for unidirectional flow in a one-dimensional channel are considered. Secondly, the region near to the die exit is then considered, and it is noted that an exponential asymptotic approach may be used to completely solve the problem of slow flow in a wedge with a sink at the vertex. Finally, the ram region of the extruder is considered and a detailed analysis is given of flow in a corner driven by the movement of one of the walls. Copyright © 1996 Elsevier Science Ltd.